2019
DOI: 10.54172/mjsc.v34i1.78
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pulp Stones in Libyan Subpopulation: A Panoramic Radiographic Study

Abstract: The aims of this study were to evaluate the prevalence of pulp stones in permanent posterior teeth of a group of adult Libyan dental patients using digital panoramic radiographs. Materials and Methods: Panoramic radiographs of 1200 adult patients (600 females and 600 males) were examined retrospectively to determine the prevalence and distribution of the pulp stones. All posterior teeth were investigated except third molars, and the data obtained were recorded as present or absent according to gender, tooth ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 36 publications
5
9
0
Order By: Relevance
“…[ 8 19 22 24 33 ] Only a few studies showed a greater number of the PS on the right side of the arch. [ 7 20 23 ] However, none of the studies showed any significant association with the PS regarding the side of the arch, which is also supporting the current outcome.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…[ 8 19 22 24 33 ] Only a few studies showed a greater number of the PS on the right side of the arch. [ 7 20 23 ] However, none of the studies showed any significant association with the PS regarding the side of the arch, which is also supporting the current outcome.…”
Section: Discussionsupporting
confidence: 82%
“…There were many studies conducted in the past for PS identification using radiographic records. [ 19-21 23-25 28 29 ] However, most of the studies used traditional 2D radiographs such as panoramic, periapical, and bitewing. The diameter of the PS needs to be a minimum of 200 μm to detect in the 2D radiographs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Turkey, Tassoker et al [5] identified pulp stones in 52% of the subjects and 7.7% of the teeth, while Sezgin et al [29] found that 24.2% of the patients and 3.3% of teeth had at least one pulp stone. In Libya, Alawjali [30] discovered pulp stones in 30.2% of the patients and 8.4% of the teeth. However, a study by Hsieh et al [13] on a Taiwanese population revealed a higher prevalence of pulp stones, than the present study, in 83.3% of the subjects and 31.3% of the of the teeth.…”
Section: Discussionmentioning
confidence: 99%